The Effect of Workload and Motivation on Employee Performance at CV. Biliva Nature Indonesia - Imelda Puji Lestari; Fandi Fatoni (Universitas Negeri Surabaya, 2026)
This study was motivated by the suboptimal employee performance at CV. Biliva Nature Indonesia, as reflected in the differences in employee performance despite workload distribution being adjusted according to individual job responsibilities. This condition indicates that workload and motivation may influence employee performance. The study aimed to analyze the effects of workload and motivation on employee performance at CV. Biliva Nature Indonesia. A quantitative research approach with a survey method was employed. Saturated sampling was applied, involving all 54 employees as the research sample. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 26. The results revealed that workload had no significant effect on employee performance. In contrast, motivation had a positive and significant effect on employee performance. Furthermore, workload and motivation simultaneously had a significant effect on employee performance. These findings indicate that improving employee motivation plays a more dominant role in enhancing performance, while appropriate workload management remains important to ensure effective work implementation. Therefore, organizations are encouraged to strengthen employee motivation and manage workload proportionally to improve overall employee performance.